A Study on the Influence of the Country of Origin on Women’s Purchasing Behavior: A Case Study of Kitenge Garment - Celestin Bimenyimana, Pierre; Ishuheri Nyamulinda, Bideri; Augustine Rugema, Habimana; Etienne, Musonera; Mutarindwa , Samuel (Social Empowerment Journal, 2025)
This study analyzes the impact of the nation of origin on women’s purchasing behaviors of Kitenge garments. A discussion with a few women was organized to gain insight into their purchasing behavior for kitenge garments, particularly in the country whose kitenge garment is preferred, and the attributes they seek when planning to buy it. Responses obtained were used to develop an instrument for the study. A sample of 100 Women was selected, considering that women are the major users of Kitenge garments. A descriptive design was employed, utilizing convenience sampling as the sampling technique. A personal interview was used as a data collection technique. The findings showed that 82 percent of respondents were aware of the presence of imported Kitenge garments in the market. Regarding the country of origin whose imported kitenge garment is preferred, respondents ranked the Netherlands first, followed by Senegal, the Democratic Republic of Congo, and the United Kingdom. Concerning the attributes that influence the purchase of Kitenge garments, the texture was ranked first, followed by the country of origin, price, appearance (color), brand name, and durability. The findings would be very useful to the local manufacturers of Kitenge as they will understand what factors influence women to buy Kitenge garments, thereby making their products more competitive. Managerial implications have also been discussed.